The Role of Microfinance in Helping the Poor: Amanah Ikhtiar Malaysia as a Model - Mahmoud Mohamed Ali Mahmoud Edris; Ahmad Syukran Baharuddin; Mohamed Sherif Bashir; Yusuf Sani Abu Bakar (DSR Publishers, The University of Jordan, 2024)
Indexed by MyCite